2010
DOI: 10.1080/00140139.2010.535024
|View full text |Cite
|
Sign up to set email alerts
|

Low back injury risks during construction with prefabricated (panelised) walls: effects of task and design factors

Abstract: New technology designed to increase productivity in residential construction may exacerbate the risk of work-related musculoskeletal disorders (WMSDs) among residential construction workers. Of interest here are panelised (prefabricated) wall systems (or panels) and facilitating an ongoing effort to provide proactive control of ergonomic exposures and risks among workers using panels. This study, which included 24 participants, estimated WMSD risks using five methods during common panel erection tasks and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…In the current study, many barriers to the PE program were outside of the contractor and worker control such as the design of the structure and project schedule. These system level issues have been recognized in other studies as caused by the architectural design that dictates the type, size, and weight of materials without regard to the methods for installation (Kim, et al, 2011, Smallwood, 2012), and limited working space for the workers (Wiberg, 2012). Other system barriers may be in the control of the construction management or general contractor (Fulmer, et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, many barriers to the PE program were outside of the contractor and worker control such as the design of the structure and project schedule. These system level issues have been recognized in other studies as caused by the architectural design that dictates the type, size, and weight of materials without regard to the methods for installation (Kim, et al, 2011, Smallwood, 2012), and limited working space for the workers (Wiberg, 2012). Other system barriers may be in the control of the construction management or general contractor (Fulmer, et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Several authors [102] created an ergonomic assessment tool using videos that allowed for postures to be assessed while working. Kim et al [100], for their part, demonstrated how the manufacture of goods from prefabricated panels negatively influenced the spinal column of the workers.…”
Section: Activities Of Households As Employers; Undifferentiated Goodmentioning
confidence: 99%
“…McGorry and Lin [14] used the RULA method to compare and demonstrate the utility of a proposed methodology that evaluates arm posture and grip strength in tool handling. Kim et al [15] used the REBA method to estimate the risk of WMSDs in panel erection to improve panel specifications and workplace design. Using the RULA and REBA body part diagrams, a risk score and its prescribed action level for ergonomic intervention can be found.…”
Section: Literature Reviewmentioning
confidence: 99%